WEBINAR ILMIAH GAMBARAN MRI TULANG BELAKANG PADA KASUS HNP, DAN KESELAMATAN PASIEN PADA MODALITAS MRI - Annisa, Aulia; Bisra, Marido; Indrapuri, R. Sri Ayu; Mismar, Devi Putri (Awal Bros Journal of Community Development, 2025)
This scientific webinar aims to provide a comprehensive overview of the use of Magnetic Resonance Imaging (MRI) in the diagnosis of herniated nucleus pulposus (HNP) and explain important safety measures for patients undergoing MRI examinations. MRI has become one of the most important imaging modalities in diagnosing HNP cases. The presentation will cover the basic principles of spinal MRI, including image acquisition techniques and interpretation of results. Different types of HNP will be discussed, including intervertebral discs and associated spinal anatomical changes. In addition, the webinar will highlight the importance of patient safety in MRI procedures. This includes a discussion of the potential risks of strong magnetic fields, contraindications, and safety protocols that should be followed by patients and medical staff. Practical steps to minimize risks and optimize examination results will be discussed in detail. By presenting experts in the field, this webinar will provide an in-depth understanding of the use of MRI in HNP cases and emphasize the importance of patient safety during the procedure. This will provide valuable insights for medical professionals involved in the care of patients with spinal problems